HUBUNGAN SELF-MANAGEMENT DENGAN KUALITAS HIDUP PADA PASIEN PASCA STROKE NON HEMORAGIK DI RUMAH SAKIT UMUM IMELDA PEKERJA INDONESIA MEDAN TAHUN 2021 - Aureliya Hutagaol; Resa Indayani Tindaon (Program Studi S1/DIII-Keperawatan Universitas Imelda Medan, 2022)
Stroke or Cerebro Vascular Accident (CVA) is a vocal or global functional brain disorder (neurological deficit) that lasts more than 24 hours caused by a neotraumatic cerebral blood circulation disorder resulting in a lack of blood and oxygen flow to the brain. as a result of blockage, narrowing or rupture of blood vessels, usually affects patients aged 40-80 years. The symptoms of stroke include headaches, loss of balance, visual disturbances, loss of the ability to speak clearly or the ability to understand other people's speech, and impaired smell. The purpose of this study was to determine the relationship between self-management and quality of life in postoperative patients. non-hemorrhagic stroke. This research was conducted at Imelda Indonesian Workers General Hospital Medan. The population in this study were 48 who were taken using accidental sampling. Data collection using a questionnaire and analyzed by Chi-square test. The results showed that p value = 0.005 < 0.05. It means that there is a relationship between self-management and quality of life in non-hemorrhagic post-stroke patients at Imelda Indonesian Workers General Hospital in Medan. Based on the results of the study, it can be concluded that the better the treatment and self-management in post-stroke patients, the lower the incidence of recurrent stroke.